'Maybe If You Talk to Her about It': Intensive Mothering Expectations and Heritage Language Maintenance - Torsh, Hanna Irving (Multilingua, 2022)
Maintaining heritage languages is frequently desired by migrants to continue cultural and social connections to family and identity. However, in imagined monolingual nations such as Australia, efforts to transmit minority languages are seen as a private matter and largely unsupported. Transmission of culture and language is also frequently seen as women's work (Heller, Monica & Laurette Lévy. 1992. Mixed marriage: Life on the linguistic frontier. "Multilingua" 11(1). 32). This article seeks to explore how linguistically intermarried heterosexual couples orient to the task of heritage language maintenance along gender lines. It draws on a qualitative interview-based study into 22 couples living in Sydney. For the English-speaking background parents in the study, pressure to raise bilingual children arising out of a discourse of "intensive mothering" (Hays, Sharon. 1996. "The cultural contradictions of motherhood." New Haven: Yale University Press) was experienced in more negative ways by mothers than fathers. The analysis points to the effects of the non-migrant partner's first language and their gender on heritage language efforts in linguistically intermarried families, and their impact on the (dis)continuation of linguistic diversity.